PERAN BP4 KECAMATAN TEBET PADA PELAKSANAAN PERKAWINAN DI INDONESIA SAAT PANDEMI COVID-19 - Hafidhah Aurelia Afrah; Khairani Bakri (Fakultas Hukum Universitas Trisakti, 2021)
The Advisory Board for the Development and Preservation of Marriage (BP4) was formed as a partner of the Ministry of Religion in creating a sakinah, mawaddah, warahmah family. The problems are: what were the problems faced by BP4 Tebet District, South Jakarta regarding the implementation of marriages in Indonesia during the Covid-19 pandemic? And what is the role of BP4 in dealing with legal issues related to the implementation of marriages in Indonesia during the Covid19 pandemic? This research is normative, descriptive analytical research, using secondary and primary data, and using qualitative analysis with deductive conclusions drawn. Conclusion: there are 6 legal issues related to unregistered marriage, underage marriage, kafa'ah, medical examination for the bride and groom, violation of sighat taklik divorce, and divorce pronounced outside the court. The role that BP4 Tebet District has to carry out with this problem is to continue to follow the efforts and efforts that have been listed in the AD/ART BP4 results. Suggestions from this research: legislators so that the Marriage Law and KHI are updated by adding health check requirements and BP4 need to add other parties such as the parents of the prospective bride and groom to attend marriage guidance.